A proposal for the regulation of the spectrum usage fee in 5G private network using fuzzy AHP - Alfin Hikmaturokhman; Kasmad Ariansyah (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2023)
This study evaluates the types of regulation models for The Indonesia Spectrum Usage Fee—the so-called Biaya Hak Pengguna (BHP) Frequency in 5G private network technology that are most suitable for implementation in Indonesia by implementing the Fuzzy Analytical Hierarchy Process (F-AHP) method. This method accommodates the opinions of telecommunications experts from mobile network operators (MNOs), regulators, vertical industries, and telecommunications consultants through a series of scientific steps to produce weights for each type of alternative solution offered. The results obtained show that the proposed model most suitable for implementation in Indonesia, taking into account the given criteria, is the one that uses unlicensed 5G frequencies. This model involves vertical industries not using licensed frequencies established by the government but rather choosing to use unlicensed frequencies to develop 5G technology for their own use. The implementation of this model is expected to encourage the optimization of regulation for Spectrum Usage Fee in 5G private network technology owned by the government, providing opportunities for vertical industries to develop 5G technology on private networks independently without relying on existing MNOs. This can stimulate innovation and technological progress in Indonesia to support Industry 4.0.